Absolute Neutrophil Count in the Peripheral Blood Predicts Prognosis in Lung Cancer Patients Treated with Anlotinib - Chen, Rong; Lu, Fang-Ying; Liu, Bing; Huang, Jingwen; Zhou, Min; Dai, Ranran; Guo, Yi (Cancer management and research, 2021)
Anlotinib is a multi-targeted tyrosine kinase inhibitor that inhibits tumor angiogenesis and cell proliferation. It is widely used as a third-line therapy for lung cancer. However, reliable prognostic biomarkers for predicting the efficacy of anlotinib are lacking. We conducted a retrospective study to investigate the prognostic value of serological inflammatory biomarkers in anlotinib treatment. Patients with advanced lung cancer treated with anlotinib monotherapy were enrolled. Cox regression was conducted to analyze the significant factors related to progression-free survival (PFS) and overall survival (OS). The objective response rate (ORR) was compared based on the median cut-off value of the significant inflammation index. Meanwhile, we created survival curves to compare the two groups and performed receiver operating characteristic curve analysis to assess the predictive ability of the inflammation index. Among a total of 71 patients, the median PFS was 5.5 months and the median OS was 9.5 months. The ORR and disease control rate were 16.9% and 84.5%, respectively. According to univariate and multivariate analyses, absolute neutrophil count (ANC) was the only indicator associated with both PFS (hazard ratio [HR] =1.095, 95% confidence interval [CI] 1.030-1.163, P=0.003) and OS (HR=1.057, 95% CI 1.003-1.113, P=0.037). In the group with ANC ≥4.58, the ORR was relatively lower (8.1% vs 26.5%, P=0.057), but not statistically significant; PFS and OS were relatively shorter (median PFS 5.0 [95% CI 4.4-9.6] vs 7.0 months [95% CI 4.4-5.7], P=0.024 and median OS 7.3 [95% CI 4.7-10.0] vs 17.6 months [95% CI 12.3-22.9], P < 0.001). ANC had a relatively high discriminatory ability to predict 10-month survival, with an area under the curve of 0.729, sensitivity of 82.5%, and specificity of 67.7%. Elevated pre-treatment ANC was associated with a poor prognosis. Patients with lower peripheral blood levels of ANC might benefit from anlotinib.